Qiroati Method Program Management in Developing the Quality of Quran Reading for Students - Royyanah, Ni’matur; Leksono, Aris Adi (Chalim Journal of Teaching and Learning, 2024)
This research uses a qualitative approach with case studies in several educational institutions and Qur'an learning centers that apply the Qiroati method. Data was collected through observation, interviews, and analysis of documents related to existing learning programs. Data analysis is carried out with content analysis techniques. The results of this study indicate that the Qiroati method has a positive impact on the development of the quality of Qur'an reading. By integrating aspects of tajweed and tafsir, learners can understand the meaning and law of tajweed contained in each verse of the Qur'an. Learning programs that adopt the Qiroati method are also able to provide a more immersive and interactive learning experience, helping learners overcome difficulties in reading the Qur'an correctly. However, challenges also arise in implementing the Qiroati method, such as the need for teachers who are skilled in tajweed and tafsir, as well as the development of learning materials that follow the students' comprehension behavior. Therefore, it is recommended that there is a holistic approach in designing learning programs, as well as continuous training for teachers to maximize the potential of the Qiroati method in improving the quality of Qur'an reading.